2022
DOI: 10.3390/nu14030494
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Oral Immune Modulation in Cow Milk Allergy

Abstract: Aim: The present study analyzed clinical and biological factors that might predict achievement of tolerance in patients with IgE-mediated cow milk allergy (CMA). Method: Seventy patients with IgE-mediated CMA (44.24 ± 24.16 months) were included in the study. The patients were evaluated clinically through skin prick test and sIgE to whole milk, casein, beta-lactoglobulin and alpha-lactalbumin. An eviction diet of 6 months was established, followed by oral food challenge test (OFC) and oral immunotherapy (OIT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…However, it has been suggested that of higher levels of CM-sIgE, greater wheal diameter and a high basophil activity decrease the likelihood of reaching tolerance [28]. Evaluation of these factors before initiating therapeutic therapy can help predict the success of CM-OIT [29].…”
Section: Key Pointsmentioning
confidence: 99%
“…However, it has been suggested that of higher levels of CM-sIgE, greater wheal diameter and a high basophil activity decrease the likelihood of reaching tolerance [28]. Evaluation of these factors before initiating therapeutic therapy can help predict the success of CM-OIT [29].…”
Section: Key Pointsmentioning
confidence: 99%
“…Молоко, содержащее -казеин А1, вызывает более выраженное ухудшение желудочно-кишечных симптомов и увеличение времени транзита через желудочно-кишечный тракт у людей с непереносимостью лактозы, чем у толерантных к лактозе, тогда как молоко, содержащее β-казеин А2, не усугубляет симптомы при непереносимости лактозы (82)(83)(84). Это свидетельствует о том, что у некоторых людей с непереносимостью лактозы неблагоприятные желудочно-кишечные симптомы после употребления молока могут быть связаны с присутствием в нем β-казеина A1, а не с самой лактозой (76,85,86).…”
Section: рис 2 первичная последовательность для наиболее распростране...unclassified
“…The role of sIgE as a potential predictive biomarker has been investigated in several food AIT studies. A recent study with 70 allergic children to CM showed that high baseline levels of sIgE to CM and casein are associated with persistence of CM allergy despite AIT [ 163 ]. This is consistent with the findings of Cohen et al [ 164 ] and Kauppila et al [ 165 ], demonstrating that elevated baseline levels of sIgE to total CM and its allergens are associated with a lower chance of reaching a maintenance dose of 200 mL of CM due to adverse reactions.…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 99%
“…However, this association was not found in a peanut AIT study with 120 participants, which could be due to the recruitment criterium of SPT wheal diameter of ≥5 mm above the negative control instead of the conventional ≥3 mm [ 155 ]. Furthermore, the SPT wheal diameter was not a predictive marker for AIT outcome in a recent study with 70 CM-allergic children undergoing AIT or a more rapid introduction of baked milk [ 163 ]. Collectively, the contradictory results of these studies suggest that more work is needed to confirm the role of SPT wheal diameter as a predictive biomarker in AIT.…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 99%